The impact of urban growth on agricultural and rural non-farm growth in Kenya - Binswanger-Mkhize, Hans P.; Johnson, Timothy; Samboko, Paul Chimuka; You, Liangzhi (2017)
To estimate the impact of urban growth on agricultural and rural nonfarm income growth we develop an urban gravity variable that reflects the economic activity of a city– total nighttime light emitted – which is a proxy income of each city. The light intensities were transformed into urban gravity variables depending on the distance of sample villages from the city, and their growth rates used for the analysis in regression equations. The key findings are as follows: Equal urban growth in all locations has an elasticity of 0.50 on agricultural income growth, and of 0.19 on rural non-farm income growth. Urban growth also has a large effect on education, followed by commercialization and then on the use of modern varieties. These in turn have a strong impact on agricultural and rural non-farm income. National urban growth has a larger impact on agricultural and rural non-farm growth than local urban growth. Once we account for the other control variables (roads, education, commercialization, modern varieties), the urban growth impact on agricultural growth is cut in half and for rural non-farm growth the urban growth impact disappears. For non-farm income almost the full impact of urban growth can be explained by its impacts on education. The elasticities of urban growth with respect to agricultural incomes via education, commercialization and HYV are 0.12, 0.10 and 0.05 respectively. Curiously, we cannot show an impact of agricultural growth on rural non-farm income growth.